Compressed sensing reconstruction algorithm based on adaptive acceleration forward-backward pursuit - Zuozhou PAN; Zong MENG; Jing LI; Ying SHI (Tongxin xuebao)
Aiming at the long running time problem of the traditional forward-backward pursuit (FBP) algorithm,an adaptive acceleration forward-backward pursuit (AAFBP) algorithm was proposed.The reconstruction process of AAFBP algorithm can be divided into two stages.In the forward stage,the AAFBP algorithm used the adaptive threshold to select the right amount of atoms to join the support set.In the backward stage,based on the projection coefficient of the atoms,the deletion threshold was introduced to remove the atoms adaptively and the excessive backtracking phenomenon in adaptive process was overcome simultaneously.The proposed method can ensure the number of the selected atoms more random,and more right atoms were retained in each iteration.The simulation results of one-dimensional sparse signal and two-dimensional image show that the AAFBP algorithm has more advantages in both the accuracy of reconstruction and the running time.